Early Complications of Total Laryngectomy: A Retrospective Study - Maharjan, R; Adhikari, P; Khalilullah, S; Sinha, BK; Baskota, DK (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Keywords: Laryngeal cancer; total laryngectomy; early complications DOI: 10.3126/njenthns.v1i2.4759 Nepalese J ENT Head Neck Surg Vol.1 No.2 (2010) p.17-18